1980
DOI: 10.1002/1097-0142(19800301)45:5<1029::aid-cncr2820450533>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Racial and socioeconomic factors in cancer survival. A comparison of veterans administration results with selected studies

Abstract: The survival experience of 46,000 Veterans Administration (VA) male cancer patients was analyzed and compared with the results of three other studies. In the VA data, no significant differences were found between white and black patient cancer survival rates except for bladder cancer; this observation differs from those in other studies. In the VA, all patients receive the same treatment with no distinctions whereas most W. S. hospitals place their patients into categories based on ability to pay. This factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 6 publications
0
30
1
Order By: Relevance
“…18,19 The current results also are consistent with findings from two other studies that included only VA patients. 25,26 No survival differences were found between black patients and white patients for several malignancies, including lung carcinoma. 25,26 The speculation was that the equal access to health care within the VA may have eliminated the racial differences in survival.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…18,19 The current results also are consistent with findings from two other studies that included only VA patients. 25,26 No survival differences were found between black patients and white patients for several malignancies, including lung carcinoma. 25,26 The speculation was that the equal access to health care within the VA may have eliminated the racial differences in survival.…”
Section: Discussionmentioning
confidence: 94%
“…25,26 No survival differences were found between black patients and white patients for several malignancies, including lung carcinoma. 25,26 The speculation was that the equal access to health care within the VA may have eliminated the racial differences in survival. However, it is also possible that, within the VA system, there may be no significant differences in socioeconomic status between blacks and whites.…”
Section: Discussionmentioning
confidence: 97%
“…In yet another study, social class explained some of the racial differences, but not all of them (Wegner et al, 1982). The confusion is not made any clearer by the fact that in some studies race has even been used as a surrogate for social class (Page & Kuntz, 1980). However, the role of the demographic factors in relation to social class cannot be assessed solely on the basis of correlation between the variables.…”
Section: Artifactual Explanationsmentioning
confidence: 99%
“…Opposite results have also been obtained. Page and Kuntz (1980) studied survival among Veterans Administration male cancer patients, and found no differences in survival by race or income except in bladder cancer. They concluded that the lack of differences was due to the fact that all the patients they studied received the same treatment with no distinctions, whereas most American hospitals placed their patients into categories on the basis of ability to pay.…”
Section: Specific Explanatory Factorsmentioning
confidence: 99%
See 1 more Smart Citation